1996
DOI: 10.1073/pnas.93.14.7022
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of oligonucleotide binding stoichiometry of gene V protein by mass spectrometry.

Abstract: The binding stoichiometry of gene V protein from bacteriophage ft to several oligonucleotides was studied using electrospray ionization-mass spectrometry (ESI-MS). Using mild mass spectrometer interface conditions that preserve noncovalent associations in solution, gene V protein was observed as dimer ions from a 10 mM NH4OAc solution.Addition of oligonucleotides resulted in formation of proteinoligonucleotide complexes with stoichiometry of approximately four nucleotides (nt) per protein monomer. A 16-mer oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 34 publications
1
74
0
Order By: Relevance
“…The mass differences between these two new ions and NodST were calculated to be 507 Da and 427 Da, which correspond to the noncolvalent adduction of PAPS and PAP, respectively. The five-fold excess of ligands was mixed with the protein so that both the binding and its specificity can be assessed [27]. Only one molecule each of the substrate (PAPS) and the inhibitor (PAP) was observed to be bound to the protein, even under the conditions of molar excess of the ligands.…”
Section: Noncovalent Complexationmentioning
confidence: 99%
“…The mass differences between these two new ions and NodST were calculated to be 507 Da and 427 Da, which correspond to the noncolvalent adduction of PAPS and PAP, respectively. The five-fold excess of ligands was mixed with the protein so that both the binding and its specificity can be assessed [27]. Only one molecule each of the substrate (PAPS) and the inhibitor (PAP) was observed to be bound to the protein, even under the conditions of molar excess of the ligands.…”
Section: Noncovalent Complexationmentioning
confidence: 99%
“…Compared with protein-ligand or multimeric protein complexes, fewer studies were reported on protein-DNA noncovalent complexes by ESI-MS [13][14][15][16][17][18], although protein-DNA interactions play essential roles in a variety of significant biological processes, such as gene-expression regulation, DNA repair and replication, and transcription regulation, etc. In the protein-DNA interactions, electrostatic forces and hydrogen bonds significantly contribute to the binding of the complex in addition to hydrophobic interactions.…”
mentioning
confidence: 99%
“…Direct ESI-MS analysis of nucleic acid complexes with other nucleic acids [106 -110], proteins [111][112][113][114][115][116], and small molecule ligands [117][118][119][120] can reveal their exact composition and stoichiometry from the observed molecular mass, dispensing with the typical curvefitting of bulk data required by spectroscopic and calorimetric methods. Unlike these techniques, MS is capable of resolving any free/bound species at equilibrium in solution, even when such species possess very similar spectroscopic characteristics.…”
Section: Elucidating Structure-function Relationshipsmentioning
confidence: 99%